Analysis of Composite Instrument Housing of Sensor Buoy Subjected to Mooring Loads. (2016) - Raj, Pravan; Venkatesan, R.; Kulkarni, S.M.; Kadiyam, Jagadeesh
Abstract: Moored data buoys are offshore platforms, fitted with meteorological and oceanographic sensors anchored at various locations in the ocean. The data is transmitted through satellite to the shore station facility. It consist of an instrument housing which is made up of aluminium 6061-T6 alloy. Several disadvantages of the current instrument housing material are its vulnerability to galvanic corrosion, maintenance cost and its heaviness. In order to avoid these shortcomings, a composite instrument housing made up of glass fibre vinyl ester (GFVE) cylinder is proposed. Two ply configurations, 22 layered with all ±90° orientation, and 22 layered with ±90° for extreme plies and ±30° for intermediate plies are analyzed for compressive service loads, in ABAQUS software package. Stress contour plot of the cylinder and ply-wise stress plots along thickness are obtained and discussed. It is concluded that that the stresses induced in cylinder with all ±90° orientation is 5.5% less than the configuration with both ±90° and ±30° at the extreme and intermediate plies respectively.